2018
DOI: 10.1002/aenm.201702619
|View full text |Cite
|
Sign up to set email alerts
|

Prussian Blue Cathode Materials for Sodium‐Ion Batteries and Other Ion Batteries

Abstract: Sodium‐ion batteries (SIBs) are considered to be a low‐cost complement or competitor to Li‐ion batteries for large‐scale electric energy storage applications; however, their development has been less successful due to the lack of suitable host materials to enable reversible Na+ insertion reactions. Prussian blue analogs (PBAs) appear to be attractive candidates for SIB cathodes because of their open channel structure, compositional and electrochemical tunability. In this paper, the authors present a comprehens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
484
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 569 publications
(490 citation statements)
references
References 162 publications
(247 reference statements)
3
484
1
2
Order By: Relevance
“…Figure a shows the voltage profiles of solid and hollow CoFe–PBA cathodes for SIBs. Even though their capacities were relatively low compared to that of other PBA cathodes in previous reports, we clearly found that the hollow nanostructure could significantly improve the sodium‐ion storage characteristics of CoFe–PBA cathode materials. Although the solid CoFe–PBA electrode showed just 12.5 mAh g −1 in the first cycle, the hollow structured CoFe–PBA electrode showed reversible capacities that were approximately two times higher than the non‐treated solid homologue in the same cycle.…”
Section: Resultscontrasting
confidence: 53%
“…Figure a shows the voltage profiles of solid and hollow CoFe–PBA cathodes for SIBs. Even though their capacities were relatively low compared to that of other PBA cathodes in previous reports, we clearly found that the hollow nanostructure could significantly improve the sodium‐ion storage characteristics of CoFe–PBA cathode materials. Although the solid CoFe–PBA electrode showed just 12.5 mAh g −1 in the first cycle, the hollow structured CoFe–PBA electrode showed reversible capacities that were approximately two times higher than the non‐treated solid homologue in the same cycle.…”
Section: Resultscontrasting
confidence: 53%
“…[56] In order to take PBAs into practical use in electrochemical energy storage, substantial enhancement of both ionic and electronic conductivity is essential. We also need to devote more efforts to understand the correlation between the reaction parameters, the final structures, and properties of the resulting materials.…”
Section: Discussionmentioning
confidence: 99%
“…Many review papers have provided insights into this field from diverse perspectives: synthetic strategies, [10][11][12][13][14][15][16][17] structural diversity, [18][19][20][21][22][23] product compositions, [24][25][26][27] and potential applications. [49][50][51][52][53][54][55][56][57] For example, when applied in rechargeable batteries, the available channels and rigid structure of the open framework make PBA materials a kind of excellent cathode materials with fast charge transfer kinetics and long cycle life. [44,45] As a result, PB and PBA materials find promising applications in catalysis, [46,47] photothermal therapy, [48] information storage, [37] sensor, [38] and energy storage and conversion.…”
Section: Introductionmentioning
confidence: 99%
“…The 3D well-known Prussian Blue family (coordination network) has been extensively described, together with its inherent magnetic, [1,2,3,4] electrode material, [5,6,7,8] porous [9] properties and applications in the field of decontamination or molecular sieves, [10] for example. They have been based either on hydrogen bonded, halogen bonded or coordination networks.…”
Section: Introductionmentioning
confidence: 99%